2018
DOI: 10.1681/asn.2018030245
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition

Abstract: Diagnosing ADTKD- by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD- and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…The large majority of ADTKD patients are carriers of mutations in UMOD or MUC1 genes 2,3 . ADTKD- REN (previously known as Familial Juvenile Hyperuricemic Nephropathy type 2 [FJHN2], MIM# 613092) represents a very rare condition, as so far 6 families have been described worldwide 47 .…”
Section: Introductionmentioning
confidence: 99%
“…The large majority of ADTKD patients are carriers of mutations in UMOD or MUC1 genes 2,3 . ADTKD- REN (previously known as Familial Juvenile Hyperuricemic Nephropathy type 2 [FJHN2], MIM# 613092) represents a very rare condition, as so far 6 families have been described worldwide 47 .…”
Section: Introductionmentioning
confidence: 99%
“…MUT Family members carried the same clinically significant variant as the proband, WT Individuals without pathogenic variants. 3,7,8,21,22 . Early studies reported only one mutation of a single cytosine insertion in the MUC1 VNTR region.…”
Section: Discussionmentioning
confidence: 99%
“…A rabbit anti-human MUC1fs polyclonal antibody was commercially prepared by Beijing Protein Innovation. A peptide antigen corresponding to 20 residues (NH2-SPRCHLGPGHQAGPGLHRPP-OH) of MUC1fs 14,16 was chemically synthesized and used to immunize rabbits for antibody production. Next, the rabbits were immunized with peptide-conjugated bovine serum albumin (BSA) by multiple intradermal injections.…”
Section: Generation Of Muc1fs Antibodiesmentioning
confidence: 99%